Solid-state interaction of ibuprofen with magnesium stearate and product characterization thereof - Stojanovska Pecova, Monika; Geskovski, Nikola; Petrushevski, Gjorgji; Chachorovska, Marina; Krsteska, Liljana; Ugarkovic, Sonja; Makreski, Petre (Informa UK Limited, 2020)
Solid-state compatibility of API with excipients is essential step in the preformulation stage of early development of new finished dosage form. Thermal analysis and vibrational spectroscopy are complementary techniques that play a pivotal role to assess the solid-state compatibility of API with excipients. Their coupling and combination with multivariate analysis, provide valuable quantitative aspect to reveal the potential interactions. The impetus of this work was aimed to fully elucidate the solid-state compatibility of ibuprofen and magnesium stearate in binary mixtures comprising pharmaceutically acceptable amounts of magnesium stearate (0.25-5% w/w). Binary mixtures were analyzed before and after exposure at strictly controlled stress conditions (25 °C/60% relative humidity and 40 °C/75% relative humidity). Interaction between ibuprofen and magnesium stearate was unambiguously confirmed. The product of their interaction was synthetized separately, characterized by means of FTIR spectroscopy, DSC, TG/DTG and XRPD for the first time and identified as diibuprofen magnesium. The induced solid-state pseudopolymorphic transition of this product to diibuprofen magnesium tetrahydrate was also studied and discussed.
Keywords: Ibuprofen; magnesium stearate; diibuprofen magnesium tetrahydrate; solid-state interaction; compatibility; mechanosynthesis